R&D behavior of German manufacturing companies during the 2008/09 recession - Alexander Eickelpasch (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper investigates to what extent the R&D behavior of manufacturing companies was influenced by the 2008/09 crisis. Based on a broad official data set for German manufacturing companies, only a few companies that engaged in R&D during 2008 gave it up in the following year. Some companies even started R&D during crisis. R&D expenditures declined in 2009 compared to 2008, but expanded in 2010. The development of R&D expenditures was less volatile than sales. Probit analyses show that the occurrence of R&D in 2009 is very much determined by engagement in R&D in 2008 and that changes in demand are not relevant. However, fluctuation in demand proved to be relevant in the regressions computed where the intensity of R&D expenditures was the dependent variable. This result suggests that companies reacted counter cyclically in 2008/09, i.e. the reduction in R&D was smaller than the decline in demand, or the expansion of R&D expenditures was greater than the change in demand. Similar regressions for using R&D staff as the dependent variable did not find any influence of changes in demand. The results suggest that companies see R&D as a longer term task necessary to retain competitiveness.
Keywords: E32; L60; O31; 330; Research and development; Business cycle; Manufacturing